A New Observation in Spiral and Curl Antenna Configurations above the Ground Plane - Hirose, Kazuhide; Hirukawa, Masayuki; Nakano, Hisamatsu (Applied Sciences, 2022)
We report here that spiral and curl antennas are essentially the same when using the moment method. This aids in the understanding and design of the two antennas, and serves as the groundwork for new ideas regarding antennas. First, the spiral antenna height above the ground plane was gradually reduced, and at each height, the spiral configuration parameters were optimized for an axial ratio of less than 0.1 dB. It was found that the spiral antenna had configuration parameters almost the same as those for a curl antenna at a height of 0.15 wavelengths. Next, the curl antenna was analyzed with a reduced height. The antenna, at a height of 0.10 wavelengths, showed a 3 dB axial ratio bandwidth of 3%, with a VSWR of less than two. The analysis results are verified with experimental results.